Potensi Wisata Alam Berbasis Anggrek Di Zona Tradisional Taman Nasional Lore Lindu (Studi Kasus Desa Karunia Kecamatan Palolo Kabupaten Sigi) - Widodo, Adhitya Sukarno; Mallombasang, Sri Ningsih; Naharuddin, Naharuddin (Mitra Sains, 2022)
This research aims to determine the feasibility of orchid-based natural tourism potential in the Karunia Village TNLL Traditional Area and determine the strategy for developing orchid-based natural tourism in the Karunia Village TNLL Area. Research was carried out through surveys and interviews equipped with a list of questions (questionnaire). Based on the research results, it is known that the potential for orchid-based natural tourism in the Karunia Village TNLL Traditional Area is worthy of being developed into a tourist destination because: (1) it has a tourist attraction in the form of an abundance of orchids both in nature and in captivity, the presence of unique and endemic flora and fauna , there is a river with protruding rocks, clear water and beautiful natural scenery, a calm and comfortable atmosphere and many variations of tourist activities that can be done. Finished. (2) lack of adequate tourist facilities, and (3) relatively easy accessibility with fairly good road conditions.